College Choice and Wages: Estimates Using Data on Female Twins - Behrman, Jere R.; Rosenzweig, Mark R.; Taubman, Paul (The Review of Economics and Statistics, 1996)
The authors assess the impact of college quality on women's earnings and the influence of family and individual endowments on college choice using new data from a survey of identical and nonidentical twins born in Minnesota. The estimates reject models that ignore school choice. The statistically preferred estimates suggest that Ph.D.-granting, private universities with well-paid senior faculty and smaller enrollments produce students who have significantly higher earnings later in life. Both the quantity of schooling and the quality of schooling resources are allocated to higher-endowed individuals, which exacerbates preexisting inequality in human capital and biases conventional estimates of school quality effects. Copyright 1996 by MIT Press.